Assessment Of The Readiness Of Multidisciplinary Healthcare Professionals To Meet The Priorities Of The “Quality Of Life Program” Within Saudi Vision 2030: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Saudi Arabia’s Vision 2030 aims to achieve a transformative shift in the healthcare system by strengthening workforce readiness and multidisciplinary collaboration under the Quality of Life Program. This systematic review synthesizes evidence on healthcare professionals’ preparedness, awareness, and barriers in aligning with Vision 2030 objectives.Methods: Guided by PRISMA 2020, ten peer-reviewed studies (2012–2025) were analyzed. Databases including PubMed, Scopus, Web of Science, and Google Scholar were searched using terms related to “readiness,” “Vision 2030,” and “healthcare professionals.” Inclusion criteria comprised studies involving healthcare workers in Saudi Arabia that assessed awareness, attitudes, and preparedness toward healthcare transformation. Data were extracted using a standardized framework and appraised with the Newcastle–Ottawa Scale and CASP tools.Results: Findings revealed moderate readiness across healthcare sectors. Awareness levels ranged from 60–80%, with higher preparedness among urban, female, and better-trained staff. Pharmacists and nurses displayed positive attitudes but lacked structured training and emotional preparedness. Major barriers included workforce shortages, inadequate managerial support, uneven digital transformation, and regional disparities. Interdisciplinary collaboration significantly improved quality of life and service delivery outcomes.Conclusion: Saudi healthcare professionals demonstrate strong willingness but partial readiness to fulfill Vision 2030’s Quality of Life goals. Addressing training deficiencies, promoting teamwork, and ensuring equitable resource allocation are essential for sustainable transformation.